FUT8 drives the proliferation and invasion of trophoblastic cells via IGF-1/IGF-1R signaling pathway. (January 2019) - Yu, Ming; Cui, Xinyuan; Wang, Hao; Liu, Jianwei; Qin, Huamin; Liu, Shuai; Yan, Qiu
Abstract: Introduction: Trophoblast proliferation and invasion are essential for embryo implantation and placentation. Protein glycosylation is one of the most common and vital post-translational modifications, regulates protein physical and biochemical properties. FUT8 is the only known fucosyltransferase responsible for catalyzing α1, 6-fucosylation in mammals, and α1, 6-fucosylated glycoproteins are found to participate in various physiopathological processes. However, whether FUT8/α1, 6-fucosylation modulates the functions of trophoblastic cells remains elusive. Methods: FUT8 in human placenta villi during 6-8 gestational weeks and trophoblastic cells were detected by Western blot and immunofluorescent staining. α1, 6-fucosylation in tissues or cells were measured by Lectin LCA ( Lens culinaris ) fluorescent staining and Lectin blot. FUT8 expression was down-regulated by siRNA transfection in JAR and JEG-3 cells, and cell viability, motility and invasiveness ability were detected by the functional experiments. α1, 6-fucosylation of insulin-like growth factor receptor (IGF-1R) was examined by immunoprecipitation, and the amount of phosphorylated IGF-1R was detected in FUT8 down-regulated JAR cells. Results: Human placenta villi and trophoblastic cells expressed FUT8/α1, 6-fucosylation. Knockdown FUT8 by siRNA transfection suppressed the proliferation, epithelial-mesenchymal transition, migration and invasion of JAR and JEG-3 cells. Furthermore, we found that FUT8 modified the α1, 6-fucosylation of IGF-1R, and regulated IGF-1 dependent activation of IGF-1R, MAPK and PI3K/Akt signaling pathways in JAR cells. Conclusions: Our results implicate a critical role for FUT8 in maintaining the normal functions of trophoblastic cells, suggesting manipulating FUT8 may be an effective approach in pregnancy. Highlights: Human placenta villi from the first trimester express FUT8 and α1, 6-fucosylation. FUT8 facilitates the proliferation, migration and invasion of trophoblastic cells. FUT8 modifies the α1, 6-fucosylatioin of IGF-1R, and regulates the IGF-1R activation.